Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Exploring the polymorphism of foxtail millet proteins and the mechanisms of activity variations driven by varietal differences - Zeyu Peng; Jia Cao; Hongyue Zhao; Bowen Yang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Multiple benefits of biochar for remediating contaminated mining soils: heavy metal stabilization, carbon sequestration, and ecological function restoration - Yibo Cheng; Weiying Feng; Yu Wang; Fang Yang; Qingfeng Miao; Chiamin Ho; Yaoqiang Huo; Haiqing Liao (Chemical Engineering Journal, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Insight into the quality and structural mechanism of wheat noodle fortified with broken rice flour - Yaxing Xie; Weijie Qi; Ruobing Jia; Shuang Xu; Jinghan Zhang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Effects of protein structure and proteomics on the moisture migration in rice with milling degrees - Jia Cao; Zeyu Peng; Lina Sun; Ruobing Jia; Bowen Yang; Jianjun Cheng; Qingfeng Ban; Huan Wang (Food Research International, 2026)

Anammox enhanced anoxic/oxic/oxic/anoxic process for treating extremely low carbon/nitrogen ratio wastewater: Performance and mechanism at different hydraulic retention times - Qingfeng Cheng; Cheng Wang; Lichao Nengzi; Chao Liu; Erdeng Du; Mingguo Peng (Journal of Water Process Engineering, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Evolution of Asian summer monsoon and vegetation in southwestern China and their linkages with wildfire history during the Holocene - Bin Zhao; Yijia Liang; Yongjin Wang; Kan Zhao; Qingfeng Shao; Hai Cheng (Global and Planetary Change, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

Anammox enhanced anoxic/oxic/oxic/anoxic process for removing carbon, nitrogen, and phosphorus from extremely low carbon/nitrogen ratio wastewater: Feasibility, performance and mechanism - Qingfeng Cheng; Yutong Chen; Wenxing Zhao; Xujing Guo; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Bioresource Technology, 2026)

The 9.2 ka event during the early Holocene recorded by a stalagmite from Dongge Cave - Chuntong He; Bin Zhao; Yongjin Wang; Kan Zhao; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Incorporating quercetin nanocrystals in chitosan-polyvinyl alcohol composite film with cinnamon essential oil loaded Pickering emulsions for enhanced controlled release properties - Simin Fan; Dequan Zhang; Qingfeng Yang; Chaoqiao Zhu; Aurore Richel; Marie-Laure Fauconnier; Cheng Li; Ming Tian; Xin Li; Chengli Hou (Food Packaging and Shelf Life, 2025)

Late deglacial and Holocene vegetation and climate change at Lake Mapam Yumco, southwestern Tibetan Plateau - Sima Humagain; Xinmiao Lü; Liping Zhu; Qingfeng Ma; Junbo Wang; Jianting Ju; Shaohang Zhu; Jiuju Cheng; Binija Kaphle; Khum Narayan Paudayal (CATENA, 2025)

Chinese speleothem evidence of the early-mid Holocene transition and the instability of Asian summer monsoon - Bin Zhao; Yongjin Wang; Kan Zhao; Jianjun Yin; Quan Wang; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Global and Planetary Change, 2025)

The impact of milling degrees on rice quality using simultaneous rheology and FTIR techniques: Focus on starch structure - Weijie Qi; Yaxing Xie; Hongyue Zhao; Jianjun Cheng; Qingfeng Ban; Mingruo Guo (Food Chemistry, 2025)

Hydroclimate changes in southwestern China from Dark Age Cold Period to Medieval Climate Anomaly and their global teleconnections - Bin Zhao; Kan Zhao; Yaoqi He; Yongjin Wang; Qingfeng Shao; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

Corrigendum to “Investigating Hofmeister ions on rice starch gelatinization using simultaneous rheology and FTIR techniques combined with 2D correlation analysis” [Food Hydrocolloids 165 2025 111265] - Weijie Qi; Yaxing Xie; Lina Sun; Zhimo Jiang; Jianjun Cheng; Qingfeng Ban (Food Hydrocolloids, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Performance and mechanism of synchronous carbon and nitrogen removal from secondary effluent by denitrification coupled with partial-denitrification anammox - Qingfeng Cheng; Yanting Tu; Wenxing Zhao; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Journal of Cleaner Production, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Investigating Hofmeister ions on rice starch gelatinization using simultaneous rheology and FTIR techniques combined with 2D correlation analysis - Weijie Qi; Yaxing Xie; Lina Sun; Zhimo Jiang; Jianjun Cheng; Qingfeng Ban (Food Hydrocolloids, 2025)

Ecosystem Shifts and Cladocera Responses in a Freshwater Lake in Semi‐Arid Regions: The Successional Synergistic Effects of Natural and Human Factors in the Past 170 Years - Longjuan Cheng; Bin Xue; Jinliang Liu; Xiangzhen Kong; Can Zhang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Wenxiu Zheng (Journal of Biogeography, 2025)
Aim Freshwater lake ecosystems in semi‐arid regions are highly fragile and complex. However, the driving forces behind changes in temperate lake ecosystems at a regional scale in China remain largely unclear, primarily due to the lack of multidecadal to centennial regional studies. This study focuses on Hulun Lake, the largest freshwater lake in northern China's semi‐arid region, with the aim of elucidating the characteristics and driving mechanisms of freshwater lake ecosystems in such areas. Location Hulun Lake, the largest freshwater lake in northern China's semi‐arid region (48.55° ~ 49.33° N, 116.97° ~ 117.81° E). Time Period From the 1840s to 2010s AD. Major Taxa Studies Zooplankton Cladocera. Methods High‐resolution multiproxy palaeoecological data (including biological and geochemical indices), human activities parameters and observational datasets from the lake basin are used to explore ecosystem shifts and Cladocera responses in Hulun Lake, located in a semi‐arid region, over the past 170 years. The hypothesis that changes in the zooplankton Cladocera community composition within the ecosystem are driven by synergistic interactions among multiple factors was tested using effective approaches based on generalised additive models (GAM) and redundancy analysis (RDA). Results The results indicate that both internal factors (such as lake sedimentary environment, fish catches, lake water level, organic matter and nutrients) within the lake and external factors (including population, urbanisation rate and livestock husbandry) in the surrounding basin have been key drivers influencing the structure of Cladocera in Hulun Lake over the past 170 years. The originally predominant littoral Cladocera species ( Chydorus sphaericus . sl.) were replaced by planktonic (Bosminidae) since the 1980s accompanied by a decline in diversity, which corresponds with the process of eutrophication and pollution in the lake. Main Conclusions The dynamics of the Cladocera assemblages indicate that the lake ecosystem is vulnerable to further imbalance since the 2000s due to the ongoing synergistic effects of declining fishery catches, increasing livestock numbers, rising populations, urbanisation rates and declining water levels in semi‐arid regions.

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Effect of hydraulic retention time on advanced nitrogen removal performance in denitrification and partial-denitrification anammox processes: NH4+-N and organic matter from secondary influent as electron donors - Qingfeng Cheng; Jun Li; Wen-Bo Nie; Hui Tian; Lichao Nengzi; Erdeng Du; Mingguo Peng (Journal of Water Process Engineering, 2025)

Effects of mono- and divalent-ions and their strength on foaming properties of infant formula protein model system - Siyu Zhang; Qinggang Xie; Fei Wang; Yaxing Xie; Jianjun Cheng; Qingfeng Ban (Food Hydrocolloids, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

Enhanced nitrogen removal from secondary effluent of municipal wastewater using denitrification filter: Feasibility of refractory organics as a carbon source - Qingfeng Cheng; Hui Tian; Wen-Bo Nie; Jun Li; Yanting Zuo; Lichao Nengzi; Erdeng Du; Mingguo Peng (Bioresource Technology, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Influence of temperature on performance and mechanism of advanced synergistic nitrogen removal in lab-scale denitrifying filter with biogenic manganese oxides - Qingfeng Cheng; Hui Tian; Yanting Zuo; Lichao Nengzi; Erdeng Du; Mingguo Peng; Xiuwen Cheng (Chemosphere, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

Enhancing carbon fixation and suppressing bacterial chemotaxis through carbon matrix nano-selenium to mitigate emissions of antibiotic resistance genes and virulence factors from chicken manure - Weikun Guan; Lizhi Li; Cheng Zhang; Dexian Zhang; Qingfeng Xing; Dongsheng Guo; Ouyang Hongbing; Haibo Zhang (Chemical Engineering Journal, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Potential of novel zinc-based nanomaterials on the microbial community, antibiotic resistance genes, and DNA replication in animal manure - Haibo Zhang; Lizhi Li; Gangfu Chen; Nancheng Yin; Jiangao Guo; Xinrui Ni; Yixin Liu; Ke Wu; Weikun Guan; Cheng Zhang; Xiaochun Wu; Shi Wenkai; et al. (Chemical Engineering Journal, 2024)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Improvement of non-fat yogurt gel syneresis by heat-unfolded whey protein isolate/mogrosides complexes: Effect on the structural characterization through simultaneous rheological and FTIR techniques - Qingfeng Ban; Zonghao Liu; Xuan Zhang; Bo Song; Yunqing Jiang; Jianjun Cheng (Food Hydrocolloids, 2023)

Effect of high hydrostatic pressure on the edible quality, health and safety attributes of plant-based foods represented by cereals and legumes: a review - Yangyue Ding; Qingfeng Ban; Yue Wu; Yuxue Sun; Zhihao Zhou; Qi Wang; Jianjun Cheng; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2023)

Advanced synergetic nitrogen removal of municipal wastewater using oxidation products of refractory organic matters in secondary effluent by biogenic manganese oxides as carbon source - Qingfeng Cheng; Hui Tian; Xujing Guo; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Water Research, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

Study on the optimal conditions of ultrasonic strengthening phosphogypsum storage and solidification of CO2 - Yu Ma; Jianjun Sheng; Tianyu Li; Cheng Yang; Qingfeng Xiao; Rulan Yang (Sustainable Chemistry and Pharmacy, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Advanced nitrogen removal performance and microbial community structure of a lab-scale denitrifying filter with in-situ formation of biogenic manganese oxides - Qingfeng Cheng; Zongyang Liu; Yang Huang; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Journal of Environmental Management, 2023)

Association of biomass fuel use with the risk of vision impairment among Chinese older adults: a cohort study - Ying Zhou; Minzhi Xu; Pan Ke; Hongkun Di; Yong Gan; Jing Feng; Xin Meng; Cheng Su; Qingfeng Tian; Zuxun Lu (Environmental Science and Pollution Research, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Evaluating the impact of co-administered drug and disease on ripretinib exposure: A physiologically-based pharmacokinetic modeling approach - Chunyang Pan; Yifan Cheng; Qingfeng He; Min Li; Fengjiao Bu; Xiao Zhu; Xiaoyu Li; Xiaoqiang Xiang (Chemico-Biological Interactions, 2023)

Investigation on 3D fatigue crack propagation in pitch bearing raceway of offshore wind turbines - Yiming Chen; Xin Jin; Yong Yue; Shuang Wang; Huali Han; Maoshi Wen; Qingfeng Wang; Peng Cheng (Ocean Engineering, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Study on dynamic damage characteristics of coal under alternating hydraulic pressure - Qingfeng Xu; Yanbin Yu; Rulin Liu; Weimin Cheng; Haotian Yang (Bulletin of Engineering Geology and the Environment, 2021)

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Performance and microbial community profiles in pilot-scale biofilter for ammonia, iron and manganese removal at different dissolved oxygen concentrations - Qingfeng Cheng; Yang Huang; Lichao Nengzi; Jianying Liu; Jie Zhang (World Journal of Microbiology and Biotechnology, 2019)

Effective degradation of Orange G and Rhodamine B by alkali-activated hydrogen peroxide: roles of HO2− and O2·− - Daiyao Wang; Jing Zou; Huahua Cai; Yixin Huang; Fei Li; Qingfeng Cheng (Environmental Science and Pollution Research, 2019)

Overexpression of VaWRKY14 increases drought tolerance in Arabidopsis by modulating the expression of stress-related genes - Langlang Zhang; Jun Cheng; Xiaoming Sun; Tingting Zhao; Mingjun Li; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2018)

Delivery of Helicobacter pylori HpaA to gastrointestinal mucosal immune sites using Lactococcus lactis and its immune efficacy in mice - Rongguang Zhang; Chen Wang; Wenbin Cheng; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan (Biotechnology Letters, 2018)

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Comparison of the Therapeutic Effectiveness of Sustained Low-Efficiency Dialysis (SLED) with Continuous Blood Purification (CBP) in Critically Ill Patients - Junzhang Cheng; Shouliang Hu; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Transgenic mice with overexpression of mutated human optineurin(E50K) in the retina - Qingfeng Meng; Zheng Xiao; Huiping Yuan; Fei Xue; Yuanmao Zhu; Xinrong Zhou; Binbin Yang; Jingbo Sun; Bo Meng; Xian Sun; Fang Cheng (Molecular Biology Reports, 2012)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Analysis of Nitrosamines Migration from Condoms in the Chinese Market Using a Proper Migration Experiment - Di Feng; Qingfeng Zhou; Xuelian Cheng; Jiedong Wang; Quanli Yang (Bulletin of Environmental Contamination and Toxicology, 2010)